Formation of massive stars under protostellar radiation feedback: very metal-poor stars. Issue 1 (9th July 2020) - Fukushima, Hajime; Hosokawa, Takashi; Chiaki, Gen; Omukai, Kazuyuki; Yoshida, Naoki; Kuiper, Rolf
ABSTRACT: We study the formation of very metal-poor stars under protostellar radiative feedback effect. We use cosmological simulations to identify low-mass dark matter haloes and star-forming gas clouds within them. We then follow protostar formation and the subsequent long-term mass accretion phase of over one million years using two-dimensional radiation-hydrodynamics simulations. We show that the critical physical process that sets the final mass is the formation and expansion of a bipolar H ii region. The process is similar to the formation of massive primordial stars, but radiation pressure exerted on dust grains also contributes to halting the accretion flow in the low-metallicity case. We find that the net feedback effect in the case with metallicity Z  = 10 −2  Z⊙ is stronger than in the case with Z  ∼ 1 Z⊙ . With decreasing metallicity, the radiation-pressure effect becomes weaker, but photoionization heating of the circumstellar gas is more efficient owing to the reduced dust attenuation. In the case with Z  = 10 −2  Z⊙, the central star grows as massive as 200 solar masses, similarly to the case of primordial star formation. We conclude that metal-poor stars with a few hundred solar masses can be formed by gas accretion despite the strong radiative feedback.